2008
DOI: 10.2341/07-74
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Intensity of Resin Composites and Dental Tissues Before and After Accelerated Aging: A Comparative Study

Abstract: This study quantitatively evaluated the fluorescence intensity of resin composites with different opacities and translucencies and determined changes in fluorescence after accelerated aging, using human enamel and dentin as controls. Six microhybrid and nanofilled composites, each in three different shades, were tested. Ten sound human incisors were used to obtain enamel and dentin specimens separately. Fluorescence measurements were obtained with a fluorescence spectrophotometer before (baseline) and after ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
80
0
10

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(97 citation statements)
references
References 20 publications
7
80
0
10
Order By: Relevance
“…Um dos fatores importantes na fluorescência presente nos materiais restauradores é devido à forma que emitem luz, fazendo com que pareçam mais brancos e brilhantes, ocasionando em uma aparência de maior vivacidade [8] .…”
Section: Introductionunclassified
“…Um dos fatores importantes na fluorescência presente nos materiais restauradores é devido à forma que emitem luz, fazendo com que pareçam mais brancos e brilhantes, ocasionando em uma aparência de maior vivacidade [8] .…”
Section: Introductionunclassified
“…Fluorescence properties of materials in the mouth can be affected by the ingress of moisture as well as by degradation over time. Some studies have reported that the fluorescence properties of composite resin materials can alter as the material ages [25,26]. When the fluorescence properties of dry and hydrated samples were compared in the present study, storage in distilled water for 8 weeks at room temperature gave lower emissions.…”
Section: Discussionmentioning
confidence: 51%
“…O uso das resinas compostas tem se difundido na prática odontológica mundial por ser um material versátil, de custo acessível e que permite ao profissional restabelecer de modo conservador a estética do sorriso tanto no segmento anterior como no posterior [1][2][3][4] .…”
Section: Introductionunclassified
“…O material restaurador ideal é o que emite luz na mesma intensidade que a dentição natural; para isso, são adicionados em sua composição pigmentos orgânicos e metais terras raras fotossensíveis à luz ultravioleta, como európio, cerium e itérbio 1,6,[9][10][11] . Porém, existem ainda dúvidas sobre o comportamento óptico das resinas compostas em relação à intensidade de fluorescência, quando comparadas entre si e com a estrutura dental, e principalmente se essa propriedade pode ser afetada por fatores, como agentes químicos, meios de imersão e polimento superficial.…”
Section: Introductionunclassified